2017
DOI: 10.1016/j.ebiom.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

How Long can we Store Blood Samples: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo assess the effect of storage time and temperature on complete blood count (CBC) and comprehensive metabolic panel (CMP) testing.MethodsPubMed, EMBASE, the Cochrane Library of Systematic Reviews, Web of Science (WOS), China National Knowledge Infrastructure (CNKI), WanFang databases and SinoMed databases were searched up to May 2017. Clinical trials with adult whole blood samples were identified. Paired reviewers independently screened, extracted data and evaluated the quality of evidence (MINORS to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 24 publications
(26 reference statements)
0
32
0
2
Order By: Relevance
“…Previous studies have stated diverse acceptable storage times for blood samples, ranging from 2 to 72 hours, depending on the degree of storage temperatures. In higher storage temperature, the acceptable storage time was shorter [9, 1519] (Fig 3). In the present study, the mean storage time was less than 2 hours (maximum 350 min) and the average storage temperatures were somewhat higher than the average room temperature (20–25 degree Celsius) which ensured the accuracy of laboratory results according to the standard.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have stated diverse acceptable storage times for blood samples, ranging from 2 to 72 hours, depending on the degree of storage temperatures. In higher storage temperature, the acceptable storage time was shorter [9, 1519] (Fig 3). In the present study, the mean storage time was less than 2 hours (maximum 350 min) and the average storage temperatures were somewhat higher than the average room temperature (20–25 degree Celsius) which ensured the accuracy of laboratory results according to the standard.…”
Section: Discussionmentioning
confidence: 99%
“…The daily processes in a laboratory generate substantial amounts of data, mostly in electronic form, that must be catalogued and archived to ensure credibility and quality of test results. Laboratory documentation must be archived efficiently to save money and space, improve productivity, allow rapid information sharing, protect patient privacy and be environmentally sustainable ( 70 - 72 ).…”
Section: Procedures 7: Archiving Of Laboratory Documentationmentioning
confidence: 99%
“…Often the extraanalytical factors such as different transportation conditions, prolonged storage at high or low temperature, improper handling that may affect analysis process are not monitored. Previous studies showed that prolonged storage of whole blood samples lead to deterioration in stability of most analytes when subjected to different time-point measurements [4,[10][11][12][13][14][15][16][17]. Studies showed stability for a wide range of plasma analytes on blood samples kept at 21 0 C [7,17].…”
Section: Introductionmentioning
confidence: 99%